“External Debt, Domestic Investment and Economic Growth in Cameroon” A system Estimation Approach - Njimanted G. Forgha; Mukete E. Mbella; Forbe H. Ngangnchi (Journal of Economics Bibliography, 2014)
The feedback of external debt on economic growth through gross domestic investment has provided quite interesting results throughout the world especially in developing countries where external and internal borrowing have been a tradition. Based on a system estimation approach, using Two Stage Least Squares as an estimation technique in the case of Cameroon for a period of 34 years (1980-2013), the results reveal that while domestic investment increases economic growth, external debt retards economic growth in Cameroon, revealing the influence of debt overhang. It was therefore concluded that external debts adversely affect economic growth in Cameroon and thus, as a major recommendation, the authorities are expected to improve on the performance of external debt through proper debt management, a complete debt relief and using the debt in productive sectors for production of goods and services.
Keywords: F40; 330; External debt; Domestic Investment; Economic growth; productive sectors